THE INFLUENCE OF BRAND AWARENESS, PROMOTION AND PRODUCT QUALITY ON CUSTOMER PURCHASING DECISION - Arif Rahman; Fajri Ariandi; Roynaldi Arista; Warsono Warsono (Jurnal Scientia, 2023)
The purpose of this research is to determine the influence of brand awareness, promotion and product quality on purchasing decisions at The Executive Ciputra Cibubur Bekasi Store. The method used is descriptive quantitative, with a population of 250 customers while the research sample consists of 100 respondents consisting of 35 men and 65 women and the sampling technique is random (probably random). In analyzing the research data, SPSS 26 was used to calculate the results of the Multiple Linear Regression variable test, t test, F test, and determination analysis. The results of this research show that based on the t test, brand awareness, promotion and product quality have a positive and significant effect on purchasing decisions, and based on the t test, brand awareness and promotion have a positive and significant effect on purchasing decisions. Based on the results of the F Test, brand awareness, promotion and product quality together have a significant influence on purchasing decisions for customers of the Ciputra Cibubur Bekasi Executive Store. Based on the results of multiple regression analysis, brand awareness, promotion and product quality only account for 74.5% of purchasing decisions, while the remaining 25.5% is influenced by other variables not examined in this research.